Penerapan Augmented Reality untuk Pembelajaran Pengenalan Hewan Mamalia di Indonesia pada TK Darul Falah - Asep Sumantri; Nabil Adrian Fadila (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Mammals are animals with the characteristics of breastfeeding, sweating, and having four limbs such as four feet, a pair of feet and hands, or a pair of wings and feet. In some kindergartens, there is an obstacle where the school targets children from disadvantaged families so that carrying out activities outside the classroom which definitely requires a lot of funds will be difficult to carry out. As technology progresses, there is technology that can help children meet their learning needs and visualizations that are very interesting to use, such as Augmented Reality.The application of augmented reality was created to help children learn to recognize mammals without needing to do activities outside of school. The implementation is carried out using the marker based tracking method accompanied by design tools using UML. The program is made in the form of an Android smartphone application.The results of this application can show mammals in three-dimensional form that is close to their original form. This will help students recognize mammals in more detail, from those that are easy to find to those that are difficult to find or even dangerous to approach.